Patients perspectives on drug shortages in six European hospital settings - a cross sectional study - Kuruc Poje, Darija; Kifer, Domagoj; Huys, Isabelle; Miranda, Joao; Jenzer, Helena; Miljković, Nenad; Hoppe-Tichy, Torsten; Bochniarz, Marcin; Frontini, Roberto; Schwartz, David G.; Vujić-Aleksić, Vesna; Nežić, Lana; et al. (BMC health services research, 2021)
BACKGROUND: It is known that drug shortages represent a major challenge for all stakeholders involved in the process, but there is little evidence regarding insights into patients' awareness and perspectives. This study aimed to investigate the patients-perceived drug shortages experience and their view on outcomes in different European hospital settings. Furthermore, we wanted to explore information preferences on drug shortages. - METHODS: A retrospective, cross sectional, a mixed method study was conducted in six European hospital settings. One hospital (H) from each of this country agreed to participate: Bosnia and Herzegovina (H-BiH), Croatia (H-CR), Germany (H-GE), Greece (H-GR), Serbia (H-SE) and Poland (H-PO). Recruitment and data collection was conducted over 27 months from November 2017 until January 2020. Overall, we surveyed 607 patients which completed paper-based questionnaire. Questions related to: general information (demographic data), basic knowledge on drug shortages, drug shortages experienced during hospitalization and information preferences on drug shortage. Differences between hospital settings were analyzed using Chi-squared test or Fisher's exact test. For more complex contingency tables, Monte Carlo simulations (N = 2000) were applied for Fisher's test. Post-hoc hospital-wise analyses were performed using Fisher's exact tests. False discovery rate was controlled using the Bonferroni method. Analyses were performed using R: a language and environment for statistical computing (v 3.6.3). - RESULTS: 6 % of patients reported experiences with drug shortages while hospitalized which led to a deterioration of their health. The majority of affected patients were hospitalized at hematology and/or oncology wards in H-BiH, H-PO and H-GE. H-BiH had the highest number of affected patients (18.1 %, N = 19/105, p < 0.001) while the fewest patients were in H-SE (1 %, N = 1/100, p = 0.001). In addition, 82.5 %, (N = 501/607) of respondents wanted to be informed of alternative treatment options if there was a drug shortage without a generic substitute available. Majority of these patients (66.4 %, N = 386/501) prefer to be informed by a healthcare professional. - CONCLUSIONS: Although drug shortages led to serious medical consequences, our findings show that most of the patients did not perceive shortages as a problem. One possible interpretation is that good hospital management practices by healthcare professionals helped to mitigate the perceived impact of shortages. Our study highlights the importance of a good communication especially between patients and healthcare professionals in whom our patients have the greatest trust.